Toward a Poetics of Disappearance: The Vanishing Commons in John Clare's "The Lament of Swordy Well" - Collings, David (Romanticism on the Net, 2019)
This essay suggests that various ideas emerging in recent ecological critique – such as the Anthropocene, the near-term extinction of humanity, and the world without us – take for granted a future human observer, even though these ideas put the existence of such a person in doubt. To take the prospect of human erasure seriously, thought must go further and think its own dissolution. It may do so in part by exploring a poetics of disappearance, a model for which this essay finds in the final stanza of John Clare's "Lament of Swordy Well."